2017
DOI: 10.1051/matecconf/201710903007
|View full text |Cite
|
Sign up to set email alerts
|

Electro Polymerization of Polypyrrole Coatings Doped with Different Proton Acids for Corrosion Protection of 304 Stainless Steel

Abstract: Abstract. Polypyrrole (PPY) coatings doped with sulphuric, oxalic and phosphoric acid were prepared on 304 stainless steel (304SS) by electropolymerization. Surface morphology and anti-corrosive performance of the polymer film was investigated by scanning electron microscope and electrochemical tests. The results indicate that the phosphoric acid doped PPY coating has a compact and smooth surface which shifts the Ecorr of 304SS towards to more positive value, while the jcorr was dropped from 10.4 to 0.88 μA cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The relevant data (in Table 2) are obtained by the extrapolation method. The inhibition efficiency η P is calculated by the following equation [22,23,24]:ηp=false(icorr0icorricorr0false)×100 where i 0 corr and i corr are the corrosion current density in 1 M HCl solutions without and with the two investigated inhibitors, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The relevant data (in Table 2) are obtained by the extrapolation method. The inhibition efficiency η P is calculated by the following equation [22,23,24]:ηp=false(icorr0icorricorr0false)×100 where i 0 corr and i corr are the corrosion current density in 1 M HCl solutions without and with the two investigated inhibitors, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among these polymers, polypyrrole (PPy) has been extensively investigated due to its physicochemical stability, high conductivity, easy processability and relatively low cost [9]. Several studies have reported that the electrosynthesis of polypyrrole (PPy) films on pure iron [10,11], mild steel [12][13][14] and stainless steel [15][16][17][18] can effectively inhibit the corrosion of these materials. It has been proposed that PPy coatings protect metallic substrates through a mixed mechanism of isolation and charge transfer [18].…”
Section: Introductionmentioning
confidence: 99%